Quantum control with smoothly varying pulses: general theory and application to charge migration - Golubev, Nikolay V.; Despré, Victor; Kuleff, Alexander I. (Journal of modern optics, 2017)
Using direct search algorithms for solving the quantum optimization problem, we demonstrate on model systems that with specifically tailored Gaussian-form laser pulses one can achieve a very good control over the dynamics in complicated quantum systems. We show that by manipulating a very limited number of laser-pulse parameters, one is able to control the charge migration process in molecules. In particular, by combining two identical Gaussian laser pulses with an appropriate delay between them, one can stop the pure electronic, few-femtosecond oscillation of the charge, redistributing it along the molecule of propiolic acid.
Gesehen am 02.10.2018